2006
DOI: 10.1074/jbc.m601201200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin J2 Alters Pro-survival and Pro-death Gene Expression Patterns and 26 S Proteasome Assembly in Human Neuroblastoma Cells

Abstract: Many neurodegenerative disorders are characterized by two pathological hallmarks: progressive loss of neurons and occurrence of inclusion bodies containing ubiquitinated proteins. Inflammation may be critical to neurodegeneration associated with ubiquitin-protein aggregates. We previously showed that prostaglandin J2 (PGJ2), one of the endogenous products of inflammation, induces neuronal death and the accumulation of ubiquitinated proteins into distinct aggregates. We now report that temporal microarray analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…Activating cAMP signaling is known to be neuroprotective [78] and to have a positive effect on the UPP [34], which in contrast is inhibited by PGJ2 [41,47,76,90]. Therefore, we explored if increasing intracellular cAMP with PACAP27 would prevent neuronal loss induced by PGJ2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activating cAMP signaling is known to be neuroprotective [78] and to have a positive effect on the UPP [34], which in contrast is inhibited by PGJ2 [41,47,76,90]. Therefore, we explored if increasing intracellular cAMP with PACAP27 would prevent neuronal loss induced by PGJ2.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, stroke and TBI increase the long-term risk for PD [8,35,73,86]. Moreover, PGJ2 impairs the ubiquitin/proteasome pathway (UPP) [41,47,76,90] and mitochondrial function [42,43,54], and potentiates dopamine toxicity [64]. Based on all of these findings we propose that PGJ2 plays an important role in PD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been showed that the cyclopentenone-type PG inhibits the ubiquitin-proteasome pathway via a decrease in the ubiquitin isopeptidase activity. 42) Wang et al 43) examined the proteasome activity by an in-gel assay and showed a PGJ 2 -dependent decline in the proteasome activity. This decline paralleled a shift in the 26 S proteasome to the 20 S core particle, indicating that PGJ 2 disrupted the assembly state of the 26 S proteasomes.…”
Section: Protein Turnovermentioning
confidence: 99%
“…Except this, (a) Immunofluorescence; (b) Hoechst 33258 Fig. 1 Expression of pirh2 protein in A549 enzymatic reactions catalyzed by a cascade of enzymes, including ubiquitin-activating enzyme E1, ubiquitinconjugated enzyme E2, and ubiquitin-ligase enzyme E3 [6,7]. Among these three enzymes, only E3 has the ability to uniquely recognize the substrate protein [8], so attention has been paid to it.…”
Section: Blocade Of A549 Cells At G 0 /G 1 and Induction Of Apoptosismentioning
confidence: 97%